The Spatial Void: Indonesia's Political Ecology of Legal Contradictions Created the humanities incident of flash floods in Sumatra’s 2025 - Muhammad Ridhwan; Hasanul Bulqiyah; Fangela Myas Sari; Lukiyana Lukiyana (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
This article examines the regulatory tensions between Law No. 23/2014 on Regional Government, which emphasizes the reconcentration of authority, and Law No. 6/2023 (the Job Creation Law), which mandates the centralization of licensing through a deregulatory framework. The study focuses on Sumatra, a region characterized by high ecological vulnerability and its role as a strategic hub for extractive expansion. Utilizing a juridical-normative methodology complemented by secondary spatial analysis, this study finds that ambiguities in environmental oversight authority have catalyzed a surge in deforestation and recurrent hydrometeorological disasters. The results demonstrate that deregulation, pursued under the guise of streamlining investment, has systematically dismantled the ecological protection functions previously vested in regional authorities. This